Antioxidant, Anti-Inflammatory, and Analgesic Activities of Aqueous Extract of Diploknema butyracea (Roxb.) H.J. Lam Bark - Sumit Bahadur Baruwal Chhetri; Deepa Khatri; Kalpana Parajuli (The Scientific World Journal)
Diploknema butyracea (Roxb.) H.J. Lam is a multipurpose tree used by the Nepalese indigenous people for medicinal purposes such as rheumatism, asthma, and ulcer and other purposes such as cooking and lighting. However, there is no scientific evidence for the medicinal uses of this plant. The present study aimed to explore the phytochemical constituents, estimate the total phenolic content, evaluate antioxidant activity, and investigate the in vivo anti-inflammatory and analgesic activities of aqueous extract of Diploknema butyracea (Roxb.) H.J. Lam bark (ADBB). Phytochemical screening was performed using standard methods. The total phenolic content was determined using the Folin–Ciocalteu method. The in vitro antioxidant activity was determined using 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay and nitric oxide radical scavenging assay. For the in vivo studies, the plant extract was given in three different doses (50, 100, and 200 mg/kg body weight) to male albino Wistar rats. Anti-inflammatory and analgesic studies were carried out using the carrageenan-induced rat paw edema and the hot plate method, respectively. Results revealed the presence of different phytoconstituents such as flavonoids, tannins, glycosides, terpenoids, and carbohydrates together with a considerable amount of phenolic compounds. Antioxidant assays indicated the potent antioxidant activity of the plant extracts. The higher dose of D. butyracea (200 mg/kg) exhibited a maximum and significant inhibition (53.20%) of rat hind paw edema volume at 4 h and showed a greater increment in latency time (12.15 ± 1.81 sec) in the hot plate test at 120 min. The present study demonstrated the antioxidant, anti-inflammatory, and analgesic potential of ADBB, which supports its traditional medicinal use.